Unveiling The Impact of “Nearpod” Application in Elevating Tenth-Grade Reading Narrative Text Comprehension Mastery - Khoirrohmah, Laelatul; Fadhilawati, Dian (Jurnal Riset dan Inovasi Pembelajaran, 2024)
This study is a Quantitative study to examine the efficacy of Nearpod application in elevating the 38 tenth-grade students' reading comprehension mastery under the topic of narrative text at SMAN 1 Bitar. Pre-experimental research using a one-group pretest and post-test design was implemented. To obtain the data, the researchers utilized the test. Before being given to the participants, the validity and reliability of the test were examined. T-tests on paired samples were used to assess the data that was gathered by applying SPSS 25. The findings showed that students' comprehension of narrative texts was much improved by using the Nearpod application. The students' post-test score of 83.05. rose from their pre-test score of 74.13 in narrative text The student's learning results throughout the pre-and post-tests differed notably, according to the matched samples t-test, with a p-value of 0.000, which was less than 0.05, indicating statistical significance. In light of these results, it is advised that English teachers incorporate Nearpod into their teaching, particularly for reading instruction. the findings suggest that Nearpod positively impacts reading instruction. Implications include the potential of Nearpod for enhancing literacy skills and promoting student engagement. Future research could explore its effectiveness across diverse student populations and grade levels, as well as comparative studies to identify best practices in literacy instruction. By addressing these areas, future research can contribute to the advancement of technology-enhanced pedagogy.